The gene pools of the grasspea (Lathyrus sativus L.) - Yunus, A. G.; Jackson, M. T. (Wiley, 1991)
Interspecific hybridization between the grasspea, Lathyrus sativus, and 15 wild species in Section Lathyrus is reported. Only two species, L. amphicarpos and L. cicera produced viable F1 hybrids with low fertility when crossed with L. sativus as male parent. Crosses with six other species produced pods following pollination when L. sativus was the male, but seedlings were inviable, seeds did not germinate or pods were empty or had totally shrivelled seeds. When L. sativus was the female parent, only one cross with L. gorgoni produced an F1, but the seedling was inviable. The germplasm resources of the grasspea are identified, with L. amphicarpos and L. cicera placed in the secondary gene pool and the other species in the tertiary gene pool. The definition of these germplasm resources is discussed in terms of grasspea improvement through plant breeding.